RADARSAT Antarctic Mapping Project: Proceedings of the Post Antarctic Imaging Campaign-I Working Group Meeting - Jezek, Kenneth C (Byrd Polar Research Center, The Ohio State University., 1998)
The Working Group Meeting was held on 18 November 1997. The University Archives has determined that this item is of continuing value to OSU's history. The RADARSAT-I Antarctic Mapping Project (RAMP) is a partnership between the Canadian Space Agency and the U.S. National Aeronautics and Space Administration. The goal of the project is to create the first, complete high-resolution radar mosaic of all of Antarctica for studies of Antarctic glaciology, geology, coastal processes and climate. The major participants in RAMP are The Ohio State University, The Alaska SAR Facility, The Jet Propulsion Laboratory and Vexcel Corporation. Phase-I of the project was the Antarctic Imaging Campaign-I (AIC-I). The AIC-I occurred during the period September 9, 1997 through October 20, 1997 and utilized the unique attributes of the Canadian RADARSAT-I to acquire the first, high-resolution, synthetic aperture imagery covering the entire Antarctic Continent. Although the primary goal of the AIC-I was the acquisition of image data, the nearly flawless execution of the mission enabled additional collections of exact repeat orbit data. These data, covering an extensive portion of the interior Antarctic, are potentially suitable for interferometric analysis of topography and surface velocity. The international Antarctic Mapping Advisory Group (AMAG) was convened on November 18, 1997 to review phase-I and to discuss phase-2 of the project, the completion of the digital mosaic. The meeting was held at the Byrd Polar Research Center of The Ohio State University. Along with members of AMAG, attendees included representatives from the Canadian Space Agency and NASA. Results of the meeting are presented in this report. This report summarizes the chronology of the AIC and describes the various data sets obtained. This report also contains a scientific assessment of the data. It was generally concluded that the RAMP data represent a new, quantitative view of Antarctica. Highlights include the discovery of new ice streams, changing locations of ice margins and the potential for using imagery as a proxy indicator of subglacial geology. This stimulated much discussion on how the data will be applied to problems of Antarctic geoscience. Future plans were also discussed. Two Antarctic Imaging Campaigns are proposed as part of the Radarsat Antarctic Mapping Project. The second AIC is tentatively scheduled to occur two years after AIC-1. However, the consensus view of the science and operational communities is to delay AIC-2 until sometime later in the RADARSAT-I program if practical. This will maximize opportunities for change detection studies. The report also addresses options for planning AIC-2 in light of the operational and scientific lessons learned from AIC-1. RAMP's extraordinary success in achieving pre-mission objectives is a result of the exceptional cooperation and commitment of many individuals in Canada and the US. This level of commitment will continue through the final map production to guarantee that the full scientific value of this rich data set is available to the international science community. Canadian Space Agency U.S. National Aeronautics and Space Administration (NASA)